1986
DOI: 10.1097/00000658-198605000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Distal Splenorenal Shunt Versus Endoscopic Sclerotherapy for Long-term Management of Variceal Bleeding

Abstract: This paper reports the preliminary results of a prospective randomized trial comparing endoscopic variceal sclerosis and distal splenorenal shunt (DSRS) in the management of patients with cirrhosis and variceal bleeding. Seventy-one patients have been entered; 36 have received sclerosis and 35 DSRS. Randomization of the study population was stratified on Child's A/B (56%) and Child's C (44%). Sixty-one per cent had alcoholic and 39% non-alcoholic cirrhosis. No patients have been lost to follow-up, which curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
5

Year Published

1987
1987
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(60 citation statements)
references
References 17 publications
5
50
0
5
Order By: Relevance
“…Initial reports of good results appeared with this therapy in the 1970s and in the first years of the 1980s; prospective randomized controlled trials were begun to compare surgical treatment with sclerotherapy. 9,10 Results varied from one trial to another but showed that survival was similar with both forms of therapy, and better bleeding control was achieved with the surgical treatment. 11 At the beginning of 1980, pharmacotherapy in the form of ␤-blockers also appeared.…”
Section: Discussionmentioning
confidence: 99%
“…Initial reports of good results appeared with this therapy in the 1970s and in the first years of the 1980s; prospective randomized controlled trials were begun to compare surgical treatment with sclerotherapy. 9,10 Results varied from one trial to another but showed that survival was similar with both forms of therapy, and better bleeding control was achieved with the surgical treatment. 11 At the beginning of 1980, pharmacotherapy in the form of ␤-blockers also appeared.…”
Section: Discussionmentioning
confidence: 99%
“…Zu ähnlichen Ergebnissen kam unsere Arbeits gruppe. die über einen Zeitraum von 10 Jahren 692 [38] Leberzirrhotiker mit rezidivierender Ösophagus-und/oder Magen varizenblutung behandelte [22,33] [20,24). Beide Shunts sind transplantationsfreundlich und schützen in Konkurrenz zu al len konservativen, endoskopischen, interventionellen und chirur gischen Verfahren am besten, sichersten und dauerhaftesten vor einer erneuten Blutung aus Ösophagus-und/oder Magenvarizen [20.…”
Section: Discussionunclassified
“…However, the incidence and severity of encephalopathy were markedly diminished after DSRS [46]. The effectiveness of DSRS has been compared to EST in three studies [47][48][49] (table 10). Rebleeding rates have al ways been lower after DSRS than after EST (11.5 vs. 47.4%).…”
Section: Complicationsmentioning
confidence: 99%